KAJIAN KOMPOSISI MEDIA DAN KONSENTRASI GA3 TERHADAP PERTUMBUHAN SEMAI DAMAR (AGATHIS LORANTHIFOLIA SALISB ) - Rahayu, Nandang (Jurnal Gamma, 2009)
This research have purpose to know an influence concentration GA3 and composition mediumabout growth sedds damar (Agathis loranthifolia Salibs), on 1 month age. This research work inGreen house, Faculty of Agriculture, University of Muhammadiyah Malang, The method of researchthat used is the factorial which stacked in the programme random of group. With 3 times repeat.Level way of treating are, concentration GA3 : A1 : control wothout GA3, A2 : 100 ppm, A3 : 200ppm, A4 : 300 ppm. Composition medium : B1 : sand : land : manure (1:1:1), B2 : sand : land :manure (2:1:2), B3 : sand : land : manure (1:2:2), B4 : sand : land : manure (2:2:1)